Palatal Health of Those Wearing Complete Dentures: For How Long Must a Tissue Conditioner and Chlorhexidine Gluconate Mouthrinse be Used? - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Objective: Palatal inflammation is usually observed in poorly cleaned dentures. The aim of this study was to retrospectively evaluate the time for which a chlorhexidine gluconate mouthrinse (CGM) and tissue conditioner (TC), which are routinely used in daily clinical practice, should be used on palatal erythema patients wearing complete dentures. Methods: Intraoral pictures taken during the clinical treatment of palatal erythemic patients were evaluated using the Budtz-Jorgensen index. Twenty-four patients wearing complete dentures who had palatal erythema were divided into three groups (n=8): Group 1 patients applied the TC only, group 2 patients, used a 0.2% CGM only, and group 3 patients used the 0.2% CGM and denture relines with the TC. The treatment duration in all groups was 14 days. Intraoral pictures were taken from the palatal area at the baseline and at 1 and 2 weeks after treatment and were evaluated using the Budtz-Jorgensen index. The chi-square test and Wilcoxon signed-Ranks test were used to compare data (p<0.05). Results: There was no statistically significant difference in inflammation levels among all groups at the baseline. All inflammation levels were severe (p>0.05). The group with the combined use of the TC and 0.2% CGM was found to be effective in reducing palatal inflammation. Conclusion: The combined use of the TC and 0.2% CGM for 2 weeks is effective in the treatment of palatal inflammation due to complete dentures.
Keywords: Palatal inflammation; complete denture; tissue conditioner; chlorhexidine gluconate mouthrinse; ORAL HYGIENE HABITS; CANDIDA-ALBICANS; STOMATITIS; EFFICACY; YEASTS; PLAQUE